Cross-Validation of the Financial Exploitation Vulnerability Scale. (17th December 2021) - Moray, Juno; Lichtenberg, Peter
Abstract: Most of the available clinical tools that detect the experience of financial exploitation (FE) are not practical for use by the many professionals who work with older adults. The available measures are often time-consuming, require specialized training to administer, or focus exclusively on the cognitive aspects of financial decision-making. The need for a brief, standardized measure of contextual risk prompted the development of the Financial Exploitation Vulnerability Scale (FEVS; Lichtenberg et al., 2020). The purpose of this study was to cross-validate the FEVS as a psychometrically sound measure of contextual risk for FE. Participants were recruited from the community (n=95), and through a financial coaching service for older adults who had experienced a financial scam (n=21). A total of 114 older adults were recruited for the study, 33 who had experienced FE and 81 who had not. An independent samples t-test demonstrated that the FEVS total score successfully differentiated older adults based on the experience of financial exploitation. The FEVS total score was correlated with age, but no other demographic factors or collected neurocognitive measures. A ROC curve detecting FE analysis revealed an area under the curve of 0.68. Internal consistency of the FEVS was a=0.80. In a logistic regression model, only the FEVS and word-reading ability were related to FE. The results of this cross-validation study are very similar to the initial study, demonstrating that the FEVS is an accessible, theory-based tool that detects the experience of FE.